THE EFFECTIVENESS OF THE ROLE OF THE SUPERVISORY BOARD OF THE CORRUPTION ERADICATION COMMISSION IN IMPLEMENTING WIRING - Bonifansius Sulimas; Eriyantouw Wahid; Rosdiana Saleh (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
The revision of Law No. 19 of 2019 on the Second Amendment to Law No. 30 of 2002 on the Corruption Eradication Commission (KPK) has raised a number of pros and cons regarding the additional articles. The existence of the Supervisory Board is considered to weaken the independence of the KPK and is at risk of expanding the authority of the addition of Article 12B, paragraph (1), which states "Wiretapping as referred to in Article 12, paragraph (1), is carried out after obtaining written permission from the supervisory board". The problem formulations in this research are: How is the regulation of wiretapping with its relation to the right to privacy right in the context of law enforcement? How is the implementation of wiretapping in Law Number 19 of 2019 and comparison with the ideal concept of wiretapping in the context of law enforcement? How is the review of the existence of a supervisory board in the judicial system in Indonesia? Furthermore, the method in this research is normative legal research, with a statutory approach, case approach, historical approach, comparative approach, and conceptual approach..